Research and Its Importance in the University Teacher’s Curriculum - Coronel Pérez, Verónica Carolina; Herrera Ávila, Yoslany Mercedes; Meza Salvatierra, Johana Katiusca; Hablich Sánchez, Félix Cristóbal (Revista Universidad de Guayaquil, 2024)
The objective of this article is to show an analysis of various studies that link research with the teaching curriculum, through a bibliographic documentary exploration that compiles studies on the subject from the last 10 years, its main conclusions are the importance of strengthening competencies. teachers of the teaching staff, their synergy through tools that allow their work together to improve the development of the department and successfully promote a research culture in the student body.